Effects of tilt interface boundary on mechanical properties of Cu/Ni nanoscale metallic multilayer composites - 杨萌 徐建刚 宋海洋 张云光 (Chinese physics B, 2015)
The effect of tilt interfaces and layer thickness of Cu/Ni multilayer nanowires on the deformation mechanism are investigated by molecular dynamics simulations. The results indicate that the plasticity of the sample with a 45° tilt angle is much better than the others. The yield stress is found to decrease with increasing the tilt angle and it reaches its lowest value at 33°. Then as the tilt angle continues to increase, the yield strength increases. Furthermore, the studies show that with the decrease of layer thickness, the yield strength gradually decreases. The study also reveals that these different deformation behaviors are associated with the glide of dislocation.